Institutional Transformation of PTKIN: Analysis of Epistemology and Integrative Curriculum Paradigm at State Islamic University - Meisya Amelia Putri; Annisa Damar Wulandari; Sutrimo Purnomo (Al-Ard: Journal of Education, 2026)
Islamic universities in Indonesia have seen notable growth along with the demands of scientific development, technological progress, and the needs of modern society. The change from Institut Agama Islam Negeri (IAIN) to Universitas Islam Negeri (UIN) is one way to update the system of higher Islamic education in Indonesia. This change is not just administrative; it also shows a shift in the scientific approach that emphasizes the integration between religious studies and general sciences. This paper aims to examine the developing ideas in the UIN environment, explain the process of its establishment and growth in Indonesia, and analyze the curriculum paradigm used in the educational system of UIN. This study uses a qualitative approach with a library research method, which involves examining various sources such as books, academic journals, and relevant documents related to the research topic. The findings show that the thinking discourse at UIN is heavily influenced by the idea of integrating knowledge, which aims to eliminate the separation between religious science and general science. In addition, the establishment of UIN was also driven by the need to expand academic research and improve the quality of Islamic education so that it can compete in the development of higher education at both national and international levels. In terms of the curriculum, UIN develops an integrated and interconnected approach that combines Islamic values with various modern academic disciplines. So, Islamic universities in Indonesia are expected to produce graduates who not only have strong religious knowledge but also academic and professional skills that match the needs of the times.